Evaluasi Praktik Pembukuan Sederhana pada UMKM Tradisional: Studi Komparatif UMKM Nasi padang dan Warung Madura - Liza Lofia Sandra; Martinus Budiantara (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to evaluate simple bookkeeping practices in traditional Micro, Small, and Medium Enterprises (MSMEs) through a comparative study between Nasi Padang and Warung Madura MSMEs. The background of this study is based on the still low level of financial literacy of MSMEs, especially in terms of recording and managing business finances, which are often not done systematically. The methods used in this activity include direct observation, simple bookkeeping training, and evaluation of the implementation of financial recording. The results of the observation indicate that Nasi Padang MSMEs have not kept complete financial records and still mix personal finances with business finances. Meanwhile, Warung Madura MSMEs have kept simple bookkeeping and separated business finances from personal finances, but the records are not organized neatly and systematically. The implementation of simple bookkeeping training has a positive impact on improving business actors' understanding in recording cash inflows and outflows and preparing simple profit and loss reports. The evaluation results show an increase in the ability of MSMEs to manage business finances in a more structured manner. Thus, simple bookkeeping plays an important role in increasing financial transparency, assisting business decision-making, and supporting the sustainability of MSMEs. This study recommends ongoing mentoring so that simple bookkeeping practices can be consistently implemented by MSMEs.